Guinea-Bissau : Second Review Under the Staff Monitored Program-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
After two years of protracted political turmoil and delays in reforms, the authorities put in place in 2021 an ambitious fiscal consolidation program to ensure debt sustainability while creating fiscal space to address vast developmental needs. In late July, Fund Management approved a 9-month Staff Monitored Program (SMP) to support the government's reform program aimed at stabilizing the economy, strengthening governance, and building a soundtrack-record of policy implementation towards an Extended Credit Facility (ECF) arrangement. The first review was concluded satisfactorily in October. A Rapid Credit Facility (RCF) disbursement of SDR 14.2 million (50 percent of quota) was approved in January to provide urgent financing to support critical spending in health and catalyze additional donor resources. The RCF disbursement, the SDR 27.2 million allocation (96 percent of quota) and reforms underpinned by the SMP are contributing to address fragility including the adverse impact of the pandemic, improve government spending transparency and mitigate debt vulnerabilities, and create conditions that would help restore donor confidence and catalyze much-needed concessional financing.